2022
DOI: 10.3389/fonc.2022.894786
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Alterations in Papillary Thyroid Carcinoma With Hashimoto’s Thyroiditis: ANK3, an Indolent Maintainer of Papillary Thyroid Carcinoma

Abstract: Hashimoto’s thyroiditis (TH) is a risk factor for the occurrence of papillary thyroid carcinoma (PTC), which is considered to be the most common type of thyroid cancer. In recent years, the prevalence of PTC with TH has been increasing, but little is known about the genetic alteration in PTC with TH. This study analyzed the mutation spectrum and mutation signature of somatic single nucleotide variants (SNV) for 10 non-tumor and tumor pair tissues of PTC with TH using whole-exome sequencing. The ANK3 protein ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…According to the literature, alterations in ANK3 and type I collagen may increase the risk of developing ureteral primary malignant melanoma ( 25 ). The ectopic expression of ANK3 significantly increased E-calcineurin expression and restricted the progression of papillary thyroid carcinoma (PTC), which suggests that ANK3 has an anti-cancer action in PTC development, and serves as the inert maintainer of PTC ( 26 ). However, Previous studies suggest the function and mechanism of ANK3 in tumor tissues are currently unknown, and need to be investigated further in future research.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, alterations in ANK3 and type I collagen may increase the risk of developing ureteral primary malignant melanoma ( 25 ). The ectopic expression of ANK3 significantly increased E-calcineurin expression and restricted the progression of papillary thyroid carcinoma (PTC), which suggests that ANK3 has an anti-cancer action in PTC development, and serves as the inert maintainer of PTC ( 26 ). However, Previous studies suggest the function and mechanism of ANK3 in tumor tissues are currently unknown, and need to be investigated further in future research.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that ANK3 regulates cell cycle and inhibits cell invasion in prostate cancer cells [14]. Overexpression of ANK3 promotes cell apoptosis and suppresses epithelial-mesenchymal transition in papillary thyroid carcinoma cells [16]. These findings indicate the prognostic value and tumor suppressive function of ANK3 in cancers.…”
Section: Introductionmentioning
confidence: 85%
“…ANK3 is the most abundant ankyrin in kidney [6] and plays a crucial role in membrane assembly, epithelial cell polarization, and regulation of ion channels [7][8][9]. In cancers, genetic and expression alterations of ANK3 have been reported in several studies [10][11][12][13][14][15][16]. Decreased ANK3 expression was associated with poor survival outcome in prostate cancer [14] and androgen receptor-positive breast cancer [15].…”
Section: Introductionmentioning
confidence: 99%
“…Among top downregulated genes, amphiregulin (AREG) is involved in EMT and growth in different types of cancer, including PDAC [80], while Adhesion G Protein-Coupled Receptor F1 (ADGRF1) has an important role in inducing quiescence and chemoresistance in breast cancer [81]. Other downregulated genes include Traf2-and Nck-interacting kinase (TNIK), involved in colorectal carcinogenesis via modulation of Wnt signaling pathway [82], and Ankyrin-3 (ANK3), whose knock-down was reported to decrease the growth of prostate cancer cells while promoting their invasion both in vitro and in vivo [83], and to inhibit invasive abilities of thyroid cancer cells and their tumorigenesis when ectopically expressed [84].…”
Section: Differential Transcriptomic Profiles In Panc-1 Cells In Resp...mentioning
confidence: 99%